Localized Aortic Dissection in a Patient with Polycystic Kidney Disease: A Case Report - Alkuraydis, Sarah A.; Allihimy, Abdulaziz S.; Smettei, Osama; Abazid, Rami M (International Journal of Innovative Research in Medical Science, 2021)
Aortic dissection (AD) is the most frequent life-threatening aortic disorder. It is commonly associated with hypertension; however, aortic dissection occasionally represents a complication of more complex syndromes. In this article we aim to report. A 40-year-old male patient, with a known case of ADPKD and a strong family history of ADPKD. He presented to the emergency department with prolonged sharp retrosternal chest pain radiating to the back and uncontrolled hypertension. Computed tomography angiography showed a localized dissection flap at the aortic root and multiple cysts in the right kidney. AD is a life-threatening condition and should be suspected in patients presenting with acute chest pain with history of ADPKD.